2011
DOI: 10.1111/j.1600-0714.2011.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytochrome P‐450 genetic polymorphisms in oral carcinogenesis

Abstract: Oral cancer is one of the most frequent head and neck cancers, and epidemiological studies have shown that smoking is a major risk factor in this pathology. However, as not all smokers develop oral cancer, some individuals must be more susceptible to develop this disease. This individual susceptibility has been related to different genetic variants in metabolizing enzymes. The cytochrome P-450 (CYP) family of enzymes metabolizes tobacco-related carcinogens producing reactive metabolites, which could cause DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 79 publications
(179 reference statements)
1
17
0
1
Order By: Relevance
“…CYP are crucial molecules for tobacco-related oral carcinogenesis [26]. We proposed that CYP may involve in the metabolism of BQ components, transform procarcinogens to DNA-reactive intermediates and contribute to oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CYP are crucial molecules for tobacco-related oral carcinogenesis [26]. We proposed that CYP may involve in the metabolism of BQ components, transform procarcinogens to DNA-reactive intermediates and contribute to oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several elegant studies that show the involvement of CYP2A6, CYP2A13, CYP1A1 and CYP1B1 in smoking/nicotine-mediated toxicity leading to various types of cancers and hepatic toxicity [38, 39]. The majority of tobacco constituents, including nicotine, are metabolized and/or activated by CYP enzymes to generate ROS and/or reactive metabolites, NNK [40]. ROS and reactive metabolites are known to cause DNA damage, lipid peroxidation and protein oxidation that leads to cell toxicity [41].…”
Section: Mechanism Of Tobacco Smoking Mediated Toxicity: Role Of Cypmentioning
confidence: 99%
“…Betel quid chewing generate a high amount of ROS, which has been implicated in multistage carcinogenesis (Soya et al, 2007). Recent studies reported a significant association between CYP1A1 polymorphism and HNC among tobacco-betel quid chewers (Anantharaman et al, 2007;Hernando-Rodriguez et al, 2012;Chaudhuri et al, 2013), whereas few studies did not found any relationship between CYP1A1 and chewing (Khlifi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%